Studi Komparasi Strategi Team Quiz dengan Two Stay Two Stray Terhadap Hasil Belajar IPS Pada Siswa Kelas III SD Muhammadiyah Terpadu Masaran Tahun 2015/2016 - Rahayu, Endang Puji (2016)
This study aims to determine (1) the difference effect between strategy team quiz with two stay two stray on learning outcomes IPS third grade students of SD Muhammadiyah Terpadu Masaran, (2) Strategies that greater influence between strategy team quiz with two stay two stray on learning outcomes IPS third grade students of SD Muhammadiyah Terpadu Masaran. This type of research is quantitative research experiment. The subjects of this study were students of class III Siti Khadijah and III Siti Aminah SD Muhammadiyah Terpadu Masaran year 2015/2016, with a total of 70 students. The technique of collecting data using interviews, tests and documentation. Data analysis technique using the t test, preceded by a test analysis as the prerequisite test for normality and homogenity test. Based on the results of data analysis with significance level of 5%, it was obtained that tcount> ttable namely 3.321> 1.995, with the average value of grade III study results Siti Khadijah greater than grade III Siti Aminah is 82.4> 72.9. The conclusion of this study were (1) there is a difference between strategy influences team quiz with two stay two stray on learning outcomes IPS third grade students of SD Muhammadiyah Terpadu Masaran; (2) Strategy team quiz has greater influence than the two stay two stray on learning outcomes IPS third grade students of SD Muhammadiyah Terpadu Masaran.